Legal Protection of Patients Who Do Care in Dental and Oral Therapists Based on Permanence No. 20 of 2016 on Permission and Maintenance of Dental Therapist Practice - Putu Ria Purnami; Purwani, Sagung Putri M.E; Kartika, I Gusti Ayu Putri; Adiyaryani, Ni Nengah (Unram Law Review, 2024)
The field of health is one that is given authority by the government in carrying out the service by dentists and oral therapists. The purpose of this paper is to analyse the legal protection of patients in dental and oral therapy, as well as the legal authority and responsibility of oral and dental therapists in providing care in accordance with their competence. This study utilizes normative law. Using a Legal and Conceptual Approach to Primary Legal Materials, Secondary Law Materials, and Tertiary Legislative Materials. The Consumer Protection Act does not fully implement the legal protection for consumer patients against dental and oral therapy practices. The authority of dental and oral therapists has been regulated in Permenkes 20 of 2016, but in practice, it is not implemented in accordance with the competence and provisions in force. The dental and oral therapist's responsibility to the patient is to give only painkillers, refer to the dentist, and provide compensation according to the rules in force.